Combination of Rescue Stenting and Antiplatelet Infusion Improved Outcomes for Acute Intracranial Atherosclerosis-Related Large-Vessel Occlusion - Baek, Jang-Hyun; Jung, Cheolkyu; Kim, Byung Moon; Heo, Ji Hoe; Kim, Dong Joon; Nam, Hyo Suk; Kim, Young Dae; Lim, Eun Hyun; Kim, Jun-Hwee; Kim, Jun Yup; Kim, Jae Hyoung (Frontiers in Neurology, 2021)
Background and Purpose: Intracranial atherosclerosis-related large-vessel occlusion caused by in situ thrombo-occlusion (ICAS-LVO) has been regarded an important reason for refractoriness to mechanical thrombectomy (MT). To achieve better outcomes for ICAS-LVO, different endovascular strategies should be explored. We aimed to investigate an optimal endovascular strategy for ICAS-LVO. Methods: We retrospectively reviewed three prospective registries of acute stroke underwent endovascular treatment. Among them, patients with ICAS-LVO were assigned to four groups based on their endovascular strategy: (1) MT alone, (2) rescue intracranial stenting after MT failure (MT-RS), (3) glycoprotein IIb/IIIa inhibitor infusion after MT failure (MT-GPI), and (4) a combination of MT-RS and MT-GPI (MT-RS+GPI). Baseline characteristics and outcomes were compared among the groups. To evaluate whether the endovascular strategy resulted in favorable outcome, multivariable analysis was also performed. Results: A total of 184 patients with ICAS-LVO were included. Twenty-four patients (13.0%) were treated with MT alone, 25 (13.6%) with MT-RS, 84 (45.7%) with MT-GPI, and 51 (27.7%) with MT-RS+GPI. The MT-RS+GPI group showed the highest recanalization efficiency (98.0%). Frequency of patent arteries on follow-up (98.0%, p < 0.001) and favorable outcome (84.3%, p < 0.001) were higher in the MT-RS+GPI group than other groups. The MT-RS+GPI strategy remained an independent factor for favorable outcome (odds ratio, 20.4; 95% confidence interval, 1.97–211.4; p = 0.012). Conclusion: Endovascular strategy was significantly associated with procedural and clinical outcomes in acute stroke by ICAS-LVO. A combination of RS and GPI infusion might be an optimal rescue modality when frontline MT fails.